RELAÇÃO DA SÍNDROME METABÓLICA E ESTRESSE OXIDATIVO EM MULHERES IDOSAS PARTICIPANTES DE GRUPOS DE CONVIVÊNCIA DA CIDADE DE SANTA MARIA - Bolzan, Aline Gurski (2018)
Introduction: Metabolic syndrome (MS) is a risk factor for the development of several comorbidities, such as atherosclerosis, diabetes mellitus, dyslipidemia, non-alcoholic hepatic steatosis, hypertension, insulin resistance, among others. Endothelial dysfunction, insulin resistance, dyslipidemia and abdominal obesity are events that may be associated with oxidative stress. This study aims to determine the relationship of MS with oxidative stress in elderly women. Methodology: This is a cross-sectional study of 79 elderly women. Blood samples were collected for the laboratory dosages of oxidative stress markers and biochemical tests related to MS. In addition, it was performed the anthropometric evaluation (weight, height, waist circumference) of the elderly women. Two articles were carried out, one relating MS to oxidative stress and the other relating nutritional status to oxidative stress. MS was classified using the criteria proposed by the National Cholesterol Education Program Adult Treatment Panel III (NCEP / ATPIII) and the nutritional status of the elderly women was classified according to Lipschitz. Oxidative damage was evaluated through the analysis of malondialdehyde (MDA) and dosages of antioxidant catalase (CAT) and glutathione (GSH) activity. Descriptive data analysis was performed using absolute and relative frequency measurements, central tendency (mean) and dispersion (standard deviation). The comparison between the means of the groups with and without MS, was evaluated by independent Student's t test and the correlations between the variables and the oxidative stress were evaluated through the Pearson correlation. These analyzes were conducted in the Statistical Package for Social Sciences (SPSS) software for Windowns version 22. p <0.05 was considered significant. Results: The mean age of the total participants was 70.3 (dp ± 8.2) years. In article 1, in which oxidative stress was associated with MS, we found a prevalence of 45.6% (n = 36) of MS. MDA levels were significantly higher in elderly women with MS and GSH levels were positively correlated with CAT activity and negatively correlated with diastolic blood pressure (DBP) in the elderly women with MS. In the elderly without MS, GSH correlated positively with body mass index (BMI) and abdominal circumference (WC) and CAT activity was positively correlated with age. MDA levels were negatively correlated with systolic blood 7 pressure (SBP). In article 2, which correlated nutritional status to oxidative stress, 57% (n = 45) of the elderly women were overweight. We found no significant difference in oxidative stress markers between the groups under study. The Pearson correlation test revealed a positive correlation between GSH levels and CAT activity and a negative correlation between GSH levels and mean DBP values. Conclusion: Our findings suggest that MS is linked to oxidative stress, demonstrated by statistically higher levels of MDA in elderly women with MS and negative correlation between GSH activity and DBP. However, overweight was not related to oxidative stress. Previous studies with the elderly are controversial, since some studies demonstrate relationship between overweight and levels of biomarkers of lipid oxidation and others not.